2020
DOI: 10.1002/tal.1704
|View full text |Cite
|
Sign up to set email alerts
|

Improving the wind‐induced human comfort of the Beijing Olympic Tower by a double‐stage pendulum tuned mass damper

Abstract: With five sub towers and a maximum height of 246.8 m, the Beijing Olympic Tower (BOT) is a landmark of Beijing. The complex structural properties and slenderness of the BOT render it prone to wind loading. As far as the wind-induced performance of this structure is concerned, this paper thus aims at a tuned mass damper-based mitigation system for controlling the wind-induced acceleration response of the BOT. To this end, the three-dimensional wind loading of various wind directions are simulated based on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Baghaei et al (2019) concluded that chamfering, roundness, tapering and set-back directly affected the drag and lift on prismatic buildings. Many of the findings were validated in the full-scale wind tunnel experiments for the John Hancock Center (Besserud et al, 2013) and the Beijing Olympic Tower (BOT) (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 86%
“…Baghaei et al (2019) concluded that chamfering, roundness, tapering and set-back directly affected the drag and lift on prismatic buildings. Many of the findings were validated in the full-scale wind tunnel experiments for the John Hancock Center (Besserud et al, 2013) and the Beijing Olympic Tower (BOT) (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 86%
“…According to equation (12), the inherent frequencies of the pendulum mass and the balls can be expressed as follows:…”
Section: Inherent Frequency Of Dtpmd-pdmentioning
confidence: 99%
“…Lu and Chen [11] analyzed along-wind responses and the wind-induced vibrating comfort of the Shanghai Center Tower with and without TMDs. Chen et al [12] proposed a double-stage pendulumtuned mass damper for the control of the wind-induced vibration of the Beijing Olympic Tower. Greco et al [13] proposed an optimum method for TMD parameters by considering both economic and performance criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy is to adopt energyabsorbing systems on buildings to dissipate seismic energy. The tuned mass damper (TMD) system is one of the most widely used systems that has been applied to many actual structures (Sadek et al 1997;Li et al 2011;Soto and Adeli 2013;Elias and Matsagar 2017;Espinoza et al 2018aEspinoza et al , 2018bZhou et al 2018;Chen et al 2019;Zhang 2019;Snamina and Orkisz 2021).…”
Section: Introductionmentioning
confidence: 99%